Manajemen mutu dalam meningkatkan pendidikan berbasis teknologi - Agustin12, Ira Nur (Maliki Interdisciplinary Journal, 2025)
The purpose of this study is to explain quality management as an improvement in education with the development of technology. Quality is one of the important aspects in education, with quality management as the main thing in facing competition in educational institutions must be comprehensive and integrated. Effective quality management can have an effect on the educational institution. Basically, the rapid development of technology is an influence in education to improve quality. This research uses a literature approach to examine the connection between quality management and technology in the context of education. The findings show that the execution of quality management in the context of technology-based education not only improves the educational process process but also prepares to face challenges in the era of globalization